PENGARUH TINGKAT LITERASI KEUANGAN SYARIAH DAN KEPERCAYAAN MASYARAKAT TERHADAP MINAT MENABUNG DI BANK SYARIAH - Nurrohmah, Resti Fadhilah; Purbayati, Radia (Jurnal Maps (Manajemen Perbankan Syariah), 2020)
The purpose of this study was to study the level of Islamic financial literacy and public confidence in the interest in saving in Islamic banks. The variables in this study are the level of Islamic financial literacy (X1), public trust (X2), and interest in saving (Y).The method of this study is descriptive quantitative approach. The data source of this study are primary data obtained by distributing questionnaires. Respondents taken are residents in the city of Bandung, with samples domiciled in the city of Bandung and at least 17 years old. The data analysis technique uses multiple linear regression analysis. The results showed that the variable level of islamic financial literacy and public trust has positive effect in the interest in saving in Islamic banks. The findings in this study provide a reference to Islamic banks, the level of literacy and public trust regarding interest in saving, therefore Islamic banks must socialize to the public.